Pendidikan Teologi Lintas Agama dalam Meraih Keluarga Bahagia (Analisis Teori Islam, Kristen, Hindu, Budha dan Konghucu) - Nur Hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This article wants to reveal cross-ideological religious education in conceptualizing a happy family. The most important thing is that religious education is very urgent in forming a family of happiness that is indoctrinated in a family. This research method uses qualitative descriptive concept, with research type of library of Risert (bibliography), data collection method is using primary and secondary data and technical data analysis is using contents analysis method (deductive and inductive). Religious education is the best way to achieve the happiness of the hereafter. Religious education is the perfect solution for achieving individual happiness, the smallest group (family) and community groups. Religious education is an easy way to achieve physical and spiritual happiness in its entirety. Religious education is a necessity for every religious community as a theory to reach the happiness of soul, family and society. Happy family will be obtained if the understanding of religion that is applied by every family member in the household and society. The happiness of society is the happiest family happiness in a country or group of people, in Islamic teachings called baldatun thayyibatun wa raobbun ghafur.